2001
DOI: 10.1021/jp012233y
|View full text |Cite
|
Sign up to set email alerts
|

A Hydrophobic Gating Mechanism for Nanopores

Abstract: Water-filled pores of nanometer dimensions play important roles in chemistry and biology, e.g., as channels through biological membranes. Biological nanopores are frequently gated, i.e., they switch between an open and a closed state. In several ion channel structures the gate is formed by a ring of hydrophobic side chains that do not physically occlude the pore. Here we investigate whether a hydrophobic pore can act as a gate via molecular dynamics simulations of the passage of water through atomistic models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
286
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 299 publications
(318 citation statements)
references
References 28 publications
(31 reference statements)
28
286
0
1
Order By: Relevance
“…The pore opens up in both directions, from its narrowest part, Ϸ3.6 Å in diameter, at the level of L44 side chains, to 7.8 Å at the N terminus and 5.8 Å at the C terminus. Hydrophobic pores are common in the known structures of gated ion channels, and the most constricted region of the pore usually is ringed by hydrophobic amino acid side chains, such as Leu or Val (38)(39)(40). The N-terminal mouth of the pore is rich in Asn, Gln, and positively charged Lys and Arg side chains, whereas the C terminus is hydrophobic.…”
Section: Fig 2 Intermonomer Distance Restraints (A)mentioning
confidence: 99%
“…The pore opens up in both directions, from its narrowest part, Ϸ3.6 Å in diameter, at the level of L44 side chains, to 7.8 Å at the N terminus and 5.8 Å at the C terminus. Hydrophobic pores are common in the known structures of gated ion channels, and the most constricted region of the pore usually is ringed by hydrophobic amino acid side chains, such as Leu or Val (38)(39)(40). The N-terminal mouth of the pore is rich in Asn, Gln, and positively charged Lys and Arg side chains, whereas the C terminus is hydrophobic.…”
Section: Fig 2 Intermonomer Distance Restraints (A)mentioning
confidence: 99%
“…18 More recently, however, it has been demonstrated in varying degrees in several systems with attractive solute-solvent interactions including smooth parallel platelike solutes, 19 atomistically resolved paraffin plates, 20 graphite plates, 21 carbon nanotubes, 22 and hydrophobic ion channels. [23][24][25] Several of these studies indicated that the magnitude of dewetting is sensitive to the nature of the solute-solvent attractive dispersion interactions. [19][20][21] A similar sensitivity was found in systems where the solutes carry charges or are exposed to an external electric field, e.g., electrostatic interactions have been shown to strongly affect the dewetting behavior of hydrophobic channels [26][27][28] and hydrophobic spherical nanosolutes.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, our solvent accessible surface should not be confused with the canonical SAS, 2 which is simply the envelope surrounding probe-inflated spheres. Similarly, phenomenological continuum theories applied to solvent dewetting always assume a certain, simplified geometry for the dry region, e.g., a cylindrical volume for systems such as hydrophobic ion channels, 24,28,40 platelike particles, 15,19 or two hydrophobic spherical solutes. 41 For a few simple systems this might be a valid approximation but for more complicated solute geometries the shape of the dewetted volume is unknown and a different approach, as suggested in this work, is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…The interest in studying such systems arises from the importance of understanding the properties of confined water and from the possibility of extrapolating the conclusions to other physical situations of similar nature, such as water adsorbed in nanopores in biological and geological systems. In recent years, Molecular Dynamics (MD) simulations have been used to study various aspects of these systems in microscopic detail [2,3,4,5,6,7,8]. Such studies complement experimental investigations by providing detailed microscopic understanding of some of the experimentally observed features.…”
Section: Introductionmentioning
confidence: 99%
“…They found that clusters of water molecules are transferred through the nanotube in the form of occasional bursts arising due to pressure fluctuations occurring outside the nanotube. Beckstein et al [3,4] have extended such simulations to 2 study the density fluctuations of water inside other hydrophobic pores. Transport of oxygen and organic molecules such as methane, ethane and ethylene through carbon nanotubes has also been studied [13,14,15,16] through MD simulations.…”
Section: Introductionmentioning
confidence: 99%